2006
DOI: 10.1038/sj.emboj.7600948
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor pleiotropy is controlled by a receptor Tyr/Ser motif that acts as a binary switch

Abstract: Pleiotropism is a hallmark of cytokines and growth factors; yet, the underlying mechanisms are not clearly understood. We have identified a motif in the granulocyte macrophage-colony-stimulating factor receptor composed of a tyrosine and a serine residue that functions as a binary switch for the independent regulation of multiple biological activities. Signalling occurs either through Ser585 at lower cytokine concentrations, leading to cell survival only, or through Tyr577 at higher cytokine concentrations, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 51 publications
2
100
0
Order By: Relevance
“…Tyr 179 of 14-3-3 Is Important for the Assembly of a PI 3-Kinase Signaling Complex in Response to Cytokine-Our findings, as well as those of others, have shown that both 14-3-3 and Shc are important for the regulation of PI 3-kinase signaling in response to GM-CSF (10,12,18). We therefore examined the possibility that the binding of Shc to Tyr 179 of 14-3-3 in response to GM-CSF stimulation may be necessary for the assembly of an active PI 3-kinase signaling complex.…”
Section: Gst-sh2mentioning
confidence: 65%
See 3 more Smart Citations
“…Tyr 179 of 14-3-3 Is Important for the Assembly of a PI 3-Kinase Signaling Complex in Response to Cytokine-Our findings, as well as those of others, have shown that both 14-3-3 and Shc are important for the regulation of PI 3-kinase signaling in response to GM-CSF (10,12,18). We therefore examined the possibility that the binding of Shc to Tyr 179 of 14-3-3 in response to GM-CSF stimulation may be necessary for the assembly of an active PI 3-kinase signaling complex.…”
Section: Gst-sh2mentioning
confidence: 65%
“…We have previously shown that there are two distinct cell survival pathways emanating from the ␤c subunit of the GM-CSF receptor: one that promotes ␤cSer 585 phosphorylation and 14-3-3 binding and the other that promotes ␤cTyr 577 phosphorylation and Shc binding (9,10). This raised the possibility that 14-3-3 and Shc may form part of a ␤c receptor-proximal signaling scaffold involved in regulating cytokine function.…”
Section: Cytokine-mediated Interaction Of Endogenous 14-3-3 and Shc-mentioning
confidence: 99%
See 2 more Smart Citations
“…Y577, Y612 and Y695 in JAK-2 were sufficient to signal proliferation. Observations in human GM-CSF responsive cell lines identified that phosphorylation of a conserved serine residue, S585, was critical for suppressing apoptosis, particularly at limiting concentrations of cytokine [42]. At low doses cells survived but did not proliferate and ßc was phosphorylated at S585 but not at Y577.…”
Section: Signalling Kinasesmentioning
confidence: 99%